# Which of the following equations can be formed using the expression x = 5:

(a) 2x + 3 = 13

(b) 3x + 2 = 13

(c) x – 5 = 1

(d) 4x – 9 = 21

**Solution:**

Let’s check each of the given equations

(a) 2x + 3 = 13

The given expression is x = 5

On multiplying both sides by 2 we get, 2x = 10

Now by adding 3 to both the sides we get, 2x + 3 = 13

Hence the equation 2x + 3 = 13 can be formed using the expression x = 5.

(b) 3x + 2 = 13

The given expression is x = 5

On multiplying both sides by 3 we get, 3x = 15

Now by adding 2 to both the sides we get, 3x + 2 = 17

Hence the equation 3x + 2 = 13 can’t be formed using the expression x = 5.

(c) x – 5 = 1

The given expression is x = 5

On subtracting 5 from both the sides we get, x – 5 = 0

Hence the equation x – 5 = 1 can’t be formed using the expression x = 5.

(d) 4x – 9 = 21

The given expression is x = 5

On multiplying both sides by 4 we get, 4x = 20

Now by subtracting 9 from both the sides we get, 4x – 9 = 11

Hence the equation 4x – 9 = 21 can’t be formed using the expression x = 5.

Thus, the correct option is (a) 2x + 3 = 13.

**✦ Try This:** Which of the following equations can be formed using the expression x = 3:

(a) 4x + 3 = 7

(b) 3x + 2 = 17

(c) x – 3 = – 6

(d) 3x – 8 = 1

Let’s check each of the given equations

(a) 4x + 3 = 7

The given expression is x = 3

On multiplying both sides by 4 we get, 4x = 12

Now by adding 3 to both the sides we get, 4x + 3 = 15

Hence the equation 4x + 3 = 7 can’t be formed using the expression x = 3.

(b) 3x + 2 = 17

The given expression is x = 3

On multiplying both sides by 3 we get, 3x = 9

Now by adding 2 to both the sides we get, 3x + 2 = 11

Hence the equation 3x + 2 = 17 can’t be formed using the expression x = 3.

(c) x – 3 = – 6

The given expression is x = 3

On subtracting 3 from both the sides we get, x – 3 = 0

Hence the equation x – 3 = – 6 can’t be formed using the expression x = 3.

(d) 3x – 8 = 1

The given expression is x = 3

On multiplying both sides by 3 we get, 3x = 9

Now by subtracting 8 from both the sides we get, 3x – 8 = 1

Hence the equation 3x – 8 = 1 can be formed using the expression x = 3.

Thus, the correct option is (d) 3x – 8 = 1.

**☛ Also Check: **NCERT Solutions for Class 7 Maths Chapter 4

**NCERT Exemplar Class 7 Maths Chapter 4 Solved Ex 3**

## Which of the following equations can be formed using the expression x = 5: (a) 2x + 3 = 13 (b) 3x + 2 = 13 (c) x – 5 = 1 (d) 4x – 9 =21

**Summary:**

Hence the equation (a) 2x + 3 = 13 can be formed using the expression x = 5

**☛ Related Questions:**

visual curriculum